Toxicity of Zn-Fe Layered Double Hydroxide to Different Organisms in the Aquatic Environment - Koba-Ucun, Olga; Olmez Hanci, Tugba; Arslan-Alaton, Idil; Arefi-Oskoui, Samira; Khataee, Alireza; Kobya, Mehmet; Orooji, Yasin (Mdpi, 2021)
The application of layered double hydroxide (LDH) nanomaterials as catalysts has attracted great interest due to their unique structural features. It also triggered the need to study their fate and behavior in the aquatic environment. In the present study, Zn-Fe nanolayered double hydroxides (Zn-Fe LDHs) were synthesized using a co-precipitation method and characterized by X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FT-IR), scanning electron microscopy (SEM), and nitrogen adsorption-desorption analyses. The toxicity of the home-made Zn-Fe LDHs catalyst was examined by employing a variety of aquatic organisms from different trophic levels, namely the marine photobacterium Vibrio fischeri, the freshwater microalga Pseudokirchneriella subcapitata, the freshwater crustacean Daphnia magna, and the duckweed Spirodela polyrhiza. From the experimental results, it was evident that the acute toxicity of the catalyst depended on the exposure time and type of selected test organism. Zn-Fe LDHs toxicity was also affected by its physical state in suspension, chemical composition, as well as interaction with the bioassay test medium.
Keywords: layered double hydroxide (LDH) catalysts; Pseudokirchneriella subcapitata; Daphnia magna; Spirodela polyrhiza; Vibrio fischeri; surface analysis; bioassays